An Experience of PBL in the Learning of Urban Planning. Chair of Urbanism IIA, FAUD, UNC, Argentine Republic - Sanchez, Monica Elisa (2020)
Within the framework of the CITYLAB LA "Engaging students with sustainable cities in Latin-America" Project, ERASMUS Program, this article reflects on the application of the Project-oriented Problem-Based Learning pedagogical method in the workshop work carried out by the Chair Urbanism IIA –Faculty of Architecture, Urbanism and Design, National University of Córdoba, Argentine Republic– in the first quarter of the school cycle 2017–, called “Urban-Territorial Plan for the Municipality of Villa Allende, Province of Córdoba. Scenario 2032”. An evaluative analysis of the results of this experience is carried out in relation to the teaching-learning process proposed by the Chair. The Chair Urbanism IIA belongs to the 5th year of the Architecture Degree and its main objective is that students develop professional competences for the study and intervention of the contemporary city as an integral fact inserted in various territorial and contextual scenarios, from the paradigm of environmental sustainability.